Eskalasi Kecemasan Sosial Akibat Adiksi Tiktok : Sebuah Studi Korelasional pada Remaja Urban di Yogyakarta - Nabilla Maharani Vadilatul Mukhlis; Mustaqim Setyo Ariyanto (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to determine the relationship between TikTok addiction and social anxiety levels in adolescents. This study uses a quantitative approach with a correlational method and involves 100 adolescents aged 13–18 years who were selected through purposive sampling. Data were collected using a Likert scale questionnaire to measure social anxiety and TikTok addiction, then analyzed using normality tests, linearity tests, and Pearson's correlation test. The results showed a significant relationship between TikTok addiction and social anxiety (p < 0.05), where the higher the TikTok addiction, the higher the social anxiety experienced by adolescents. These findings confirm that excessive use of TikTok can affect the psychological well-being and social interaction abilities of adolescents. This study suggests the development of digital literacy strategies and mental health programs in schools, as well as the active role of parents in monitoring and guiding social media use. The practical implications of these findings indicate the need for social policies and humanities-based educational programs that support the management of adolescents' social media use, thereby preventing negative impacts on their mental health and social skill development.